Pelaksanaan Aplikasi ArchiClass di Al Ayyubi Archery Club Boyolali - Faiq Yudzaikra; Suryo Saputra Perdana (Lembaga Pengembangan Kinerja Dosen, 2025)
The sport of archery requires an accurate and fair classification system of athletes according to international standards. This community service research aims to introduce and implement the ArchiClass application as a technology-based innovation for athlete classification, as well as improve the understanding of the archery community at Al Ayyubi Archery Club Boyolali regarding sports with disabilities. This activity involved 50 athletes and 6 coaches. The methods used include socialization, application demonstration, simulation, and evaluation of participant responses. The results showed that participants gained a better understanding of the importance of fair and technology-based classification. Participants gain practical experience using ArchiClass, while coaches and parents gain new insights into archery. In addition, the implementation of this application encourages the creation of a more transparent and consistent classification process. The final evaluation showed that the majority of participants felt helped by the existence of the application and expressed readiness to implement it in training activities and competitions. This program successfully introduced ArchiClass as an effective tool and increased community awareness and understanding of disability sports.